2022
DOI: 10.3390/ijms23084290
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Homing in Intrathecal Applications and Inspirations for Improvement Paths

Abstract: A transplanted stem cell homing is a directed migration from the application site to the targeted tissue. Intrathecal application of stem cells is their direct delivery to cerebrospinal fluid, which defines the homing path from the point of injection to the brain. In the case of neurodegenerative diseases, this application method has the advantage of no blood–brain barrier restriction. However, the homing efficiency still needs improvement and homing mechanisms elucidation. Analysis of current research results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Our results connote essential links between CSF cytokine levels and early improvements in ASD symptoms: regulation of cytokine patterns contributes to significant improvements in the child's behavior during the first six months. This implies the successful homing [49] of autologous BMAC and cytokines to the brain, where they acted on targeted cell types. In the brain, this immunological influx triggered neuroplasticity [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results connote essential links between CSF cytokine levels and early improvements in ASD symptoms: regulation of cytokine patterns contributes to significant improvements in the child's behavior during the first six months. This implies the successful homing [49] of autologous BMAC and cytokines to the brain, where they acted on targeted cell types. In the brain, this immunological influx triggered neuroplasticity [50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the positive healing promise and safety of cell therapies in ASD patients (Table 9) [27,31,[45][46][47][48][49][50]. However, it is hard to qualitatively compare the results between the studies due to the deployment of different evaluation metrics, cell therapy protocols, and cultural and post-treatments rehabilitation differences that may influence the results between the follow-up periods.…”
Section: Clinical Implications Of Cytokine Dynamics In Bmac Therapy F...mentioning
confidence: 99%
“…The niche produces chemotactic factors like SDF-1 to guide migration and homing of circulating stem cells back to their niche residence after injury or transplantation [23].…”
Section: Homingmentioning
confidence: 99%
“…Some transplanted stem cells demonstrate remarkable homing capacity, migrating to sites of injury or disease [23,88]. The natural niche provides molecular guidance cues facilitating such directed stem cell motility [89].…”
Section: Understanding Stem Cell Homing Mechanismsmentioning
confidence: 99%
“…Once MSCs rolled to the vascular wall, a few significant ligands related to MSC extravasation, such as CD44 (HCAM), CXCR4, and VLA-4, were triggered. The adherence process occurs when the adhesion molecule selectin ligand CD44 (HCAM) expressed by MSCs interacts with selectins located on ECs ( 94 , 95 ). Notably, CD44 is a significant target for modifying MSCs.…”
Section: Homing Functions Of Mscs In Alf Treatmentmentioning
confidence: 99%